HEAVY METALS CONCENTRATIONS IN SURFACE WATER AND SEDIMENT IN KUNDUR ISLAND COASTAL WATERS, THE PROVINCE OF RIAU ISLANDS - Febri Wando Situmorang; Bintal Amin; Syahril Nedi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted in November 2017 aimed to analyze the heavy metal concentrations in sediment and surface sea water and the relationship between them as well as to know the level of metal pollution in Kundur Island Coastal Waters, Riau Islands Province. The highest concentration of Cr in sea water was found at Station 3 (0.0598 mg/l), while in sediment was at Station 2 (30,1533 μg/g). The highest concentration of Cu in seawater was found at Station 1 (0.0296 mg/l), while in sediment was at Station 3 (1.7967μg/g). The highest concentration of Zn in seawater was found at Station 2 (0.0904 mg/l) whereas in sediment was at Station 2 (39,5050 μg/g). Simple linear regression analysis for Cr indicated that when Crconcentration in sea water increases, itsconcentrations in sediments also increases. On the contrary, when Cu and Zn concentration in water increases, their concentrations in sediments decreases and vice versa. The concentrations of Cr, Cu and Zn in seawater have exceeded the threshold value, while in the sediments their concentrations were considered as having nonegative effect to the existing organisms in these waters. Keywords: Heavy Metal, Pollution, Kundur Island, Water, Sediment